Teacher's perceptions on the development of Clitoria ternatea extracts as a learning media to enhance students' scientific creativity - Kusuma, Nanda Wiguna Putri; Fadiawati, Noor; Diawati, Chansyanah (Indonesian Journal of Science and Mathematics Education, 2024)
The advancement of the industrial revolution era has made scientific creativity an essential skill for students. Scientific creativity can be cultivated using educational media. This study aims to describe chemistry teachers' perceptions regarding the development of natural indicators from butterfly pea flower (Clitoria ternatea) extract as a learning medium to enhance scientific creativity. This research employs a mixed-method approach with a Sequential Explanatory Design involving 21 chemistry teacher respondents in Bandar Lampung. The results indicate that all respondents positively perceive the development of natural indicators from Clitoria ternatea extract as a learning medium to enhance scientific creativity, considering it accurate, easy to use, and environmentally friendly. Therefore, the developed natural indicator can be used as a learning medium to enhance students' scientific creativity. The implications of this study highlight the potential use of environmentally friendly natural indicators in educational practices to foster scientific creativity among students.